2023
DOI: 10.3847/1538-4357/acf2f4
|View full text |Cite
|
Sign up to set email alerts
|

The Accretion History of EX Lup: A Century of Bursts, Outbursts, and Quiescence

Mu-Tian 牧天 Wang 王,
Gregory J. 雷歌 Herczeg 沈,
Hui-Gen 慧根 Liu 刘
et al.

Abstract: EX Lup is the archetype for the class of young stars that undergoes repeated accretion outbursts of ∼5 mag at optical wavelengths that last for months. Despite extensive monitoring that dates back 130 yr, the accretion history of EX Lup remains mostly qualitative and has large uncertainties. We assess historical accretion rates of EX Lup by applying correlations between optical brightness and accretion, developed on multi-band magnitude photometry of the ∼2 mag optical burst in 2022. Two distinct classes of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Other studies have suggested A V = 0 mag (e.g., Sipos et al 2009). Recently, Wang et al (2023) estimated an extinction of A V = 0.1 mag toward EX Lupi. We used the conservative value of A V = 1.1 mag in our paper.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Other studies have suggested A V = 0 mag (e.g., Sipos et al 2009). Recently, Wang et al (2023) estimated an extinction of A V = 0.1 mag toward EX Lupi. We used the conservative value of A V = 1.1 mag in our paper.…”
Section: Introductionmentioning
confidence: 92%
“…It underwent three major outbursts (ΔV ∼ 5 mag) along with several small outbursts since its first reported outburst observation in the 1940s (McLaughlin 1946;Herbig 1977Herbig , 2007Bateson et al 1991;Herbig et al 2001;Aspin et al 2010;Kóspál et al 2022;Zhou & Herczeg 2022;Cruz-Sáenz de Miera et al 2023;Wang et al 2023). Recently, EX Lupi went into an accretion-driven outburst in 2022 March (Kóspál et al 2022;Zhou & Herczeg 2022;Cruz-Sáenz de Miera et al 2023;Wang et al 2023). The state of high accretion rate remained for about 100 days before returning to its preoutburst photometric state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young stellar objects (YSOs), stochastic enhancements of the accretion rate from the protoplanetary disk onto the star seem to play an important role in building up the stellar mass (Kenyon et al 1990;Offner & McKee 2011;Dunham & Vorobyov 2012;Fischer et al 2019;Lee et al 2021;Zakri et al 2022;Wang et al 2023). To some degree, these events supplement the consistent but slowly declining flow of disk mass that persists for a few million years.…”
Section: Introductionmentioning
confidence: 99%
“…To understand this, we need to determine, at least in a statistical sense, the amplitudes and durations of bursts. Recently, Wang et al (2023) presented a framework for using burst durations and amplitudes to infer what fraction of a star's mass is accreted during each mode and applied it to 70 yr of photometry of EX Lup. They concluded that the largest bursts are responsible for about half of the accreted mass during the monitoring time, with the other half arising from the combination of small bursts and quiescent accretion.…”
Section: Introductionmentioning
confidence: 99%